Acetalated-dextran as valves of mesoporous silica particles for pH responsive intracellular drug delivery. Issue 13 (14th February 2015) - Lin, Zhe; Li, Jizhen; He, Hongyan; Kuang, Huihui; Chen, Xuesi; Xie, Zhigang; Jing, Xiabin; Huang, Yubin
<x xml:space="preserve">Abstract</x> A pH-sensitive drug release system using acetalated-dextran as valves was designed to manipulate smart intracellular release of anticancer drugs.